Management of preterm labor: atosiban or nifedipine? - Roel de Heus; Eduard J H Mulder; Gerard H A Visser (Dove Medical Press, 2010)
Roel de Heus, Eduard J H Mulder, Gerard H A VisserDepartment of Woman and Baby, University Medical Centre Utrecht, The NetherlandsAbstract: Preterm birth is strongly associated with neonatal death and long-term neurological morbidity. The purpose of tocolytic drug administration is to postpone threatening preterm delivery for 48 hours to allow maximal effect of antenatal corticosteroids and maternal transportation to a center with specialized neonatal care facilities. There is uncertainty about the value of atosiban (oxytocin receptor antagonist) and nifedipine (calcium channel blocker) as first-line tocolytic drugs in the management of preterm labor. For nifedipine, concerns have been raised about unproven safety, lack of placebo-controlled trials, and its off-label use. The tocolytic efficacy of atosiban has also been questioned because of a lack of reduction in neonatal morbidity. This review discusses the available evidence, the pros and cons of either drug and aims to provide information to support a balanced choice of first-line tocolytic drug: atosiban or nifedipine?Keywords: atosiban, oxytocin receptor antagonist, nifedipine, calcium channel blocker, preterm birth, tocolytic drugs, preterm labor